Pengaruh Penggunaan dan Implementasi Teknologi Digital terhadap Perubahan Hubungan Sosial Masyarakat 4.0 - Natallios Peter Sipasulta; Dionysia Kowanda; Siti Nurafiah (Jurnal Ekonomi Manajemen Akuntansi, 2024)
The Industrial Revolution 4.0 era has brought significant changes in various aspects of life, including social relations in society. Digital technologies such as social media, the internet of things (IoT), and artificial intelligence (AI) have become an integral part of human interaction. This article aims to analyze the influence of the use and implementation of digital technology on the pattern of social relations in society. This study uses a qualitative method with an in-depth literature approach. The results of the analysis show that although digital technology provides convenience in communication, there are negative impacts such as decreased face-to-face interaction and increased social isolation.